Resúmenes (1993)
Modernización del proceso administrativo; Modernisation du processus administratif; Modernization of management process. / La cara oculta de la consultoría en los países en desarrollo; La face cachee de l'activite de conseil dans les pays en voie de developpement; The hidden side of consultancy work in developing countries. / La producción de los años 90s; La production dans les annees 90; Production in the 90s. / Educación y formación: en búsqueda de la prosperidad nacional; Education et formation: a la recherche de la prosperite nationale; Education and training: in search of the national prosperity. / Autonomía municipal y desarrollo local; Autogestion municipale et developpement local; Municipal self administration and local development. / Mercados - empresas – empresarios; Marches, enterprises, entrepreneurs; Markets - enterprises – businessmen. / Las incubadoras de empresas en Quebec; L'incubateurd'entreprises au quebec; Incubators of quebec's enterprises.